Treatment of Auto Wash Wastewater with Classical Fenton Process: Effect of Pre-Settling on COD Removal Kinetics - Hüseyin Cüce; Hakan Dulkadiroğlu; Şennur Merve Yakut; Melike Kocabaş (Doğal Afetler ve Çevre Dergisi)
In parallel with the population, the number of vehicles in traffic is increasing day by day. Therefore, the volume of wastewater generated by vehicle cleaning reaches substantial proportions. While most of these wastewaters are not classified as domestic wastewater, they are directly discharged to the sewerage. In this study, classical Fenton process was applied to remove chemical oxygen demand (COD) from 4 types (raw and pre-treated) wastewater belonging to 2 different car wash plants. At the end of experimental studies, optimum chemical doses at a constant pH = 3 value; for the sample taken from the 1nd plant without pre-settling:[Fe+ 2]= 100 mg L-1, [H2O2]= 200 mg L-1 and for the sample treated with pretreatment these values [Fe+ 2]= 75 mg L-1, [H2O2]= 150 mg L-1, for the raw wastewater sample taken from the 2nd plant, [Fe+ 2]= 100 mg L-1, [H2O2]= 225 mg L-1, after pre-settling whereas [Fe+ 2] = 75 mg L-1, [H2O2]= 100 mg L-1. COD removal in ideal conditions for the first wastewater sample is 86 percent and 89 percent, respectively, while these values are 90 percent and 98 percent for the second sample. The oxidation process in raw wastewater was found to be generally appropriate for 2nd order kinetics (R2 = 0.55 and 0.95), but the decomposition mechanism after pre-settling was found to be more consistent with the BMG kinetic model (R2 = 0.99).